The Analysis of Human Resource Management Performance during Work from Home Using Human Resource Scorecard Method - Saiful Mangngenre; Nilda Syamsul; Nurfaidah Tahir; Nurul Niswa; Nadzirah Ikasari Syamsul (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2026)
The pandemic of COVID-19 spreading in Indonesia has forced the government to create an issue; work from home (WFH) policy. WFH changed the organization's work system which was originally face-to-face to become virtually. Changes in the work system are considered to be able to affect organizational performance. Indirectly, the implementation of WFH has an impact on the performance of the organization and its human resources. This study aims to analyze the performance of the management of PT. X especially in human resources during WFH implemented by the company. Results based on the strategic objectives obtained 7 KPIs. The results of the HR Scorecard method are that there are 4 perspectives, including financial perspective, customer perspective, internal business process perspective and learning and growth perspective. By using the Analytical Hierarchy Process (AHP) method, priority performance indicators were found, namely the percentage change in performance before and after training and employee satisfaction scores. Measurement of performance indicators against supervisory targets using the Traffic Light System (TLS) gives results if there are 2 assessment indicators that meet the target and 5 assessment indicators that have not reached the target. The indicator that experienced a decline was employee training. Using the 5 whys analysis method is known to cause a decrease in employee assessment indicator; the assessment that cannot be implemented virtually.